Evaluation of quality of life in patients with post-stroke dizziness - بعجانو, أسامة; علي مزيد زريق (Latakia University Journal -Medical Sciences Series, 2024)
Stroke and the subsequent dizziness greatly affect the patient's life. It is considered one of the most common diseases and has serious consequences, severe disability, and high treatment costs. Therefore, the current descriptive study aimed to evaluate the quality of life of patients with post-stroke dizziness. This was based on an available sample of 40 stroke patients at Tishreen University Hospital in Lattakia. The data was collected using a questionnaire developed by the researcher, and The study showed more than three-quarters of patients, 77.5%, had a general quality of life at an average level, and a small percentage of them, 15% and 7%, had agood and poor quality of life, respectively. The study recommended the necessity of identifying and predicting the quality of life for post-stroke dizziness patients, which can help in early diagnosis. For patients at risk to modify these factors in order to improve their quality of life, subject them to rehabilitative training programs and support them in the process of developing effective compensation strategies to improve the restoration of central sensory integration and balance.